(untitled) (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study is to assess whether MHC class I-presented tumor antigen is appraisable for T-cell responses against ovarian cancer. In ovarian cancer cell, human leukocyte antigen A2 (HLA-A2) associated with peptides was used to promote the activation of naive T cells so as to activate antigen-specific T cells. 7 or 4 patients were observed grade 1 or 2 injection site reactions, respectively. 5, 2 or 1 patients were observed grade 1, 2 or 3 pain reactions, respectively. 4 or 1 patients were observed grade 1 or 2 induration reactions. Total number mean value of patients experiencing response to the particular peptide was 7.73, and total number mean value of peptides to which the patients responded was 7.45. MHC class I-presented tumor antigen is appraisable for T-cell responses against ovarian cancer in China.